2008
DOI: 10.1128/aac.01316-07
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Production of Phospholipase C and Perfringolysin O (Alpha and Theta Toxins) in a Gatifloxacin-Resistant Strain of Clostridium perfringens

Abstract: Clostridium perfringens-induced gas gangrene is mediated by potent extracellular toxins, especially alpha toxin (a phospholipase C [PLC]) and theta toxin (perfringolysin O [PFO], a thiol-activated cytolysin); and antibiotic-induced suppression of toxin synthesis is an important clinical goal. The production of PLC and PFO by a gatifloxacin-induced, fluoroquinolone-resistant mutant strain of C. perfringens, strain 10G, carrying a stable mutation in DNA gyrase was compared with that of the wild-type (WT) parent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Resistant strains also exhibit physiological changes that are different from wild-type strains. Similarly, we have shown in vitro that one out of five strains of C. perfringens produced a higher amount of toxin in response to gatifloxacin exposure (Rafii et al 2008). The effects of some of the most recently developed fluoroquinolones (garenoxacin, gemifloxacin, and clinafloxacin) on colonic ecology have also been evaluated (Table 4).…”
Section: Fluoroquinolonesmentioning
confidence: 87%
See 1 more Smart Citation
“…Resistant strains also exhibit physiological changes that are different from wild-type strains. Similarly, we have shown in vitro that one out of five strains of C. perfringens produced a higher amount of toxin in response to gatifloxacin exposure (Rafii et al 2008). The effects of some of the most recently developed fluoroquinolones (garenoxacin, gemifloxacin, and clinafloxacin) on colonic ecology have also been evaluated (Table 4).…”
Section: Fluoroquinolonesmentioning
confidence: 87%
“…Fluoroquinolones have been shown to induce bacteriophages and enhance Shiga toxin production in E. coli O157:H7, which may increase the virulence of this strain (Zhang et al 2000). In our laboratory, one out of five gatifloxacin-resistant Clostridium perfringens strains also had enhanced production of phospholipase C and perfringolysin O (Rafii et al 2008). Subinhibitory concentrations of ampicillin and clindamycin may directly affect adherence of Clostridium difficile by increasing the expression of genes necessary for colonization (Deneve et al 2008).…”
Section: Effects On Bacterial Pathogenicitymentioning
confidence: 98%
“…Previously we showed that different C. perfringens strains rapidly developed resistance, even to high potency fluoroquinolones, and that resistant strains had various mutations in the fluoroquinolone target genes [29]. In addition, the production of some enzymes was altered in some resistant mutants [30,31]. One gatifloxacin-resistant strain, NCTR, had increased levels of α-toxin (phospholipase C, PLC) and θ-toxin (perfringolysin O, PFO) [30].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the production of some enzymes was altered in some resistant mutants [30,31]. One gatifloxacin-resistant strain, NCTR, had increased levels of α-toxin (phospholipase C, PLC) and θ-toxin (perfringolysin O, PFO) [30]. These results point to global changes in the expression of various genes in gatifloxacin- resistant strains and to the need for further study.…”
Section: Introductionmentioning
confidence: 99%
“…25 Resistance to fluoroquinolones also affects the metabolic activities of C. perfringens, including production of toxins. 18,20 Using microarray analysis of gatifloxacinresistant (GR) mutants of C. perfringens strains NCTR and ATCC 13124, we found global changes in the expression of various genes. 15 Transcription of a variety of genes involved in all aspects of bacterial metabolism, including those coding for energy metabolism, transport, and virulence, was affected.…”
Section: Introductionmentioning
confidence: 99%